Reformers and revolutionaries: the battle for the working classes in Gibraltar and its hinterland, 1902-1921 - Grocott, Chris A.; Stockey, Gareth; Grady, Jo (Taylor & Francis, 2018)
This article examines labour organisation in Gibraltar and its hinterland from c.1902-1921. It demonstrates that the traditionally strong links which had existed between organisations in Gibraltar and neighbouring Spain - links based upon a shared belief in anarchist ideas and practices - had, by 1921, broken down due to the adoption of gradualist and constitutionalist politics and industrial relations by workers on the Rock. Two principal agents drove this change. First, in 1919, the British Workers’ Union established a branch in Gibraltar which successfully worked to establish itself as principal negotiator and representative of workers on the Rock. Second, a reforming governor in Gibraltar undertook to open up political spaces in Gibraltar which offered the potential to work with, rather than against, the state in the colony. By the end of the period, anarchism, and anarchist ideas, were not extinguished in Gibraltar, but they would never again serve as the inspiration for industrial and political campaigns on the Rock, much to the delight of both Gibraltarian employers and the British colonial authorities. This case-study invites further consideration of how British style trade union activity in the empire displaced indigenous forms of organising, a subject which has heretofore received scant attention.